Etika Akademik dalam Perspektif Islam (Menerapkan Nilai-Nilai Al-Qur'an dan Hadits dalam Penelitian dan Pendidikan) - Husni Mubarok, Arif (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
Academic ethics cannot be separated from the important role of Islamic education, Islamic education based on the Qur'an and hadith regulates the relationship of something with other elements, which can ensure harmony and harmony in life to achieve outward progress and spiritual happiness, the academic world is expected to provide intelligent solutions to problems that occur in society universally guided by academic ethics. Academic ethics is the nature of scientific activities that take place in the academic world both in educational institutions apply universally, such as honesty, thoroughness, openness, objectivity, humility, willingness to learn and develop ready to accept criticism, mutual respect and not apply discrimination. Violations of academic ethics are things that tarnish the world of education. violations of academic ethics must be analyzed for causes and solutions, as for actions that violate academic ethics must be taken seriously through solutions and prevention efforts.